Religion and Local Cultural Identity in Indonesia’s Plural Society: A Sociological Thematic Synthesis - Ronald Sianipar; Kesumawati Kesumawati; Mawilis Bin Sulihbai; Krisbianto Anes; Aprilius Nahak (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2026)
Religion is deeply involved in the construction and transmission of local cultural identity in Indonesia. However, its relationship with local culture is neither uniformly integrative nor inherently conflictual. Previous studies have documented particular communities, traditions, and religious encounters, but the mechanisms through which religion contributes to cultural continuity, social integration, and contestation remain insufficiently synthesized. This article examines how religion participates in the formation, maintenance, and transformation of local cultural identity in Indonesia’s plural society. It uses a qualitative structured thematic review of scholarly publications located through Google Scholar, Garuda, and Crossref using Indonesian and English search terms. The review primarily covers publications from 2016 to 2025 while retaining earlier works required for conceptual and historical interpretation. The sources were analyzed across four domains: normative values, ritual and symbolic practices, institutional mediation, and cultural adaptation or contestation. The analysis identifies four connected mechanisms. Religious values supply moral frameworks for interpreting communal life; rituals and symbols embody collective belonging; religious and cultural institutions authorize and transmit shared meanings; and adaptive negotiation enables communities to respond to social and cultural change. These mechanisms can support integration when communities sustain reciprocal participation, institutional recognition, and negotiated coexistence. They may also reinforce social boundaries when authority is concentrated, local practices are delegitimized, or political interests intensify religious differentiation. The article develops a conditional sociological account of religion–culture relations that avoids treating religion as either an automatic source of harmony or an inevitable cause of conflict.